Applicability of TB-LAMP test for diagnosis of pulmonary TB among HIV-positive individuals - B. Muriithi; M.M. Bundi; T. Moriyasu; A. Ahmed; M. Mwamzuka; M. Karama; S. Kaneko (IJTLD Open)
BACKGROUND: The loop-mediated isothermal amplification for TB (TB-LAMP) assay is more cost-effective and accessible than the Xpert ® MTB/RIF assay. This study aimed to evaluate the diagnostic performance of the TB-LAMP assay in individuals with and without HIV infection. METHODS: Patients aged ≥15 years presenting with symptoms of TB were included in the study. The TB-LAMP assay was performed alongside routine TB diagnostic methods, including the Xpert assay and smear microscopy, to evaluate discrepancies in test results and associated factors. RESULTS: A total of 903 patients were enrolled in the study. The positive percentage agreement for smear microscopy and TB-LAMP compared with the Xpert assay was respectively 54.3% (95% CI 46.6–61.8) and 76.6% (95% CI 69.9–82.6). Among HIV-positive individuals, the positive percentage agreement was 42.5% (95% CI 32.9–52.4) for smear microscopy and 68.9% (95% CI 59.1–77.5) for TB-LAMP. Factors such as age >60 years (adjusted OR 3.29, 95% CI 0.32–33.83), loss of appetite (aOR 0.30, 95% CI 0.13–0.70), and HIV-positive status (aOR 3.29, 95% CI 1.12–9.63) were associated with discrepancies between TB-LAMP and Xpert results. CONCLUSIONS: TB-LAMP demonstrated better agreement with the Xpert assay compared with smear microscopy in detecting TB among HIV-positive patients, suggesting that TB-LAMP could effectively replace smear microscopy.